The Role of Volunteering in Social Innovation in a Peripheral Area. Evidence from a Case Study (European journal of volunteering and community-based projects, 2025)
This article examines how volunteering contributes to social innovation in a marginalized territory, specifically Calabria. To achieve this objective, we conduct a case study on the Castrovillari section of the Italian Red Cross (CRI), which has been actively engaged in social development projects in the Alto Tirreno Cosentino area for years. The findings highlight the crucial role of volunteer organizations in fostering social innovation in disadvantaged regions, raising social awareness, and addressing Calabria’s structural social challenges. This study contributes to exploring volunteering in a region with unique social dynamics shaped by its peripheral location, a context that has been largely overlooked in the literature. The analysis underscores the need for further investigation into the social and economic dynamics of marginalized communities in Italy and Europe. Additionally, it provides practical implications by identifying effective strategies for sustainability and social impact while recommending that policymakers enhance support for volunteer initiatives.
Keywords: Volunteering; Social Innovation; case study; Calabria